The low-luminosity Type II SN2016aqf: a well-monitored spectral evolution of the Ni/Fe abundance ratio - Muller-Bravo TE (OXFORD UNIV PRESS, 2022)
Low-luminosity Type II supernovae (LL SNe II) make up the low explosion energy end of core-collapse SNe, but their study and physical understanding remain limited. We present SN 2016aqf, an LL SN II with extensive spectral and photometric coverage. We measure a V-band peak magnitude of -14.58 mag, a plateau duration of similar to 100 d, and an inferred Ni-56 mass of 0.008 +/- 0.002 M-circle dot. The peak bolometric luminosity, L-bol approximate to 10(41.4) erg s(-1), and its spectral evolution are typical of other SNe in the class. Using our late-time spectra, we measure the [O I] lambda lambda 6300, 6364 lines, which we compare against SN II spectral synthesis models to constrain the progenitor zero-age main-sequence mass. We find this to be 12 +/- 3 M-circle dot. Our extensive late-time spectral coverage of the [Fe II] lambda 7155 and [Ni II] lambda 7378 lines permits a measurement of the Ni/Fe abundance ratio, a parameter sensitive to the inner progenitor structure and explosion mechanism dynamics. We measure a constant abundance ratio evolution of 0.081(-0.010)(+0.009) and argue that the best epochs to measure the ratio are at similar to 200-300 d after explosion. We place this measurement in the context of a large sample of SNe II and compare against various physical, light-curve, and spectral parameters, in search of trends that might allow indirect ways of constraining this ratio. We do not find correlations predicted by theoretical models; however, this may be the result of the exact choice of parameters and explosion mechanism in the models, the simplicity of them, and/or primordial contamination in the measured abundance ratio.